Challenging Texts With Violence Toward Women: Lamentations and Comfort Woman in Feminist Postcolonial Perspective - Ku, Eliana Ah-Rum (Journal of feminist studies in religion, 2023)
Postcolonial feminist hermeneutics presents many challenges to the traditional interpretation of Bible passages. Recognizing the ethical issues in Old Testament metaphors about unclean and unfaithful women, readers now contemplate how to understand and accept in modern times these texts that reveal disenfranchised and excluded voices. This study deals with the violence inflicted on women under the guise of reasonable punishment and its unavoidable results as these are narrated in cultural contexts. This study uses a postcolonial feminist perspective to examine how the book of Lamentations and the novel Comfort Woman reveal the violence, oppression, and forced silence imposed on women. In addition, through finding the value in both the witness to and resistance to suffering, as well as through exploring participation in suffering, this study probes how to dismantle the structure of colonialism that reduces women to victims and offers an alternative reading of the biblical script that in the past has justified violence against women.